NATURAL INHIBITORS IN SOUS VIDE COOKING - A CRITICAL REVIEW - Mîşu, Georgiana Ancuta; Munteanu-Ichim, Roxana-Andreea; Canja, Cristina Maria; Lupu, Mirabela; Matei, Florentina (Scientific Papers. Series D. Animal Science, 2024)
Sous vide (SV), a culinary technique that involves vacuum sealing food and cooking it at precise temperatures, has been celebrated for improving food's texture, flavor, and nutritional content. Integrating natural inhibitors is a crucial strategy for enhancing food safety, shelf life, and health benefits by fighting microbial growth. This review examines the combined effects of SV and natural inhibitors on various food types, including meats, seafood, and vegetables. It highlights significant progress in food safety, with natural additives helping to reduce pathogen resistance and curb bacterial spread, thus improving the overall safety and sensory appeal of meals. Moreover, it discusses the challenges and opportunities in refining the use of natural inhibitors in SV cooking, such as achieving the right balance between flavor and microbial management. The adoption of SV varies globally, reflecting its adaptability in different culinary traditions. The review suggests future research avenues, like exploring new natural inhibitors, cooking conditions, and their effects on consumer health, emphasizing SV's role in modernizing cooking practices to meet demands for quality, and safety.
Keywords: culinary innovation; food safety; natural inhibitors; sensory quality; sous-vide